Molecular phylogeny of the limacoid snail family Dyakiidae in Southeast Asia, with the description of a new genus and species. Issue 1 (3rd December 2020) - Jirapatrasilp, Parin; Tongkerd, Piyoros; Jeratthitikul, Ekgachai; Liew, Thor-Seng; Pholyotha, Arthit; Sutcharit, Chirasak; Panha, Somsak
Abstract: Members of the terrestrial snail family Dyakiidae from Southeast Asia show a distinct geographical distribution pattern and possess different degrees of complexity in their amatorial organ gland. This study is the first molecular phylogeny of ten of the 12 genera in this family, performed to provide insights into the origin of Dyakiidae and the evolution of their shells and amatorial organ gland structure. A new genus and new species, Pseudoquantula lenticularis Jirapatrasilp & Panha gen. & sp. nov., was uncovered based on its distinct morphological characters and molecular divergence. All other genera were retrieved as monophyletic except for Dyakia . Mainland Southeast Asia was inferred to be the ancestral range of the Dyakiidae, and the lineages then dispersed to and diversified in Borneo. Cladistic analysis showed that all 14 morphological characters used in this study were homoplastic. These results disagree with the previous amatorial organ transformation series, in which neither Pseudoplecta nor Quantula was ancestral to the other genera. The enigmatic genus Pseudoplecta, which lacks an amatorial organ gland, exhibited secondary loss.